MODEL HALAMAN TUNGGAL UNTUK PENINGKATAN KINERJA APLIKASI PEREKAMAN DATA PENUGASAN JABATAN STRUKTURAL - Husni Thamrin (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2017)
Convenience is one of the key factors that support the success of information system implementation, and it is affected by how the system supports users to quickly get their job done. For the case of institution XYZ, the process of data recording of a managerial mutation requires a number of steps. System operators found it cumbersome to go through too many steps when recording such data because it takes a long time to complete the task. The situation is exacerbated for recording a decree with several job assignment changes. To overcome this problem, we have developed an application that applies single page model and replaced the legacy system that applies standard web pages. The use of a single page web-based applications reduces the amount of data that are transferred between client and server so it is more efficient in terms of processing speed compared to the standard web application. The implementation of single page application in institution XYZ drops the number of data transfered to the level of 62% for recording a single job assignment. The percentage level is smaller when a process contains a lot of job assignment, as happened in the case of large-scale mutation.Keywords: single page application, job assignment, information systemKenyamanan penggunaan sistem informasi merupakan salah satu faktor kesuksesan implementasi sistem, dan hal ini dipengaruhi oleh dukungan sistem agar pengguna dapat menyelesaikan pekerjaan dengan cepat. Proses perekaman data pergantian jabatan struktural pada aplikasi yang diterapkan di lembaga XYZ memerlukan beberapa tahap aktivitas untuk setiap data jabatan baru. Teknik ini memberi masalah terutama ketika merekam sebuah surat keputusan dengan banyak perubahan data penugasan,  yaitu lamanya waktu untuk menyelesaikan pekerjaan. Untuk mengatasi permasalahan tersebut, diterapkan model halaman tunggal menggantikan model halaman web standar. Penggunaan model halaman tunggal pada aplikasi berbasis web mengurangi jumlah data yang harus ditransfer antara server dan client sehingga lebih efisien dari segi kecepatan proses dibanding penerapan model halaman standar. Pada aplikasi yang diterapkan di lembaga XYZ, perekaman satu data jabatan dengan model halaman tunggal memerlukan hanya 62% jumlah data yang ditransfer antara client dan server. Prosentase akan mengecil jika sebuah proses mengandung banyak data penugasan, seperti yang terjadi dalam kasus mutasi jabatan besar-besaran.Kata kunci: aplikasi halaman tunggal, single page application, penugasan jabatan, sistem informasi